Antibiotikaanvändning vid kirurgisk behandling av pyometra hos hund - Larsson, Sara (2018)
Pyometra is defined as a bacterial uterine infection with accumulation of pus in the lumen. The disease affects middle-aged to older non-spayed female dogs. Pyometra is a serious disease which can lead to life-threatening complications such as peritonitis and sepsis. In some parts of the world, peri-operative antimicrobial therapy is recommended to all dogs with pyometra. In Sweden, peri-operative antibiotics is only recommended to bitches with peritonitis, sepsis or moderate to severely affected general condition. Antibiotics can save lives because of its ability to kill bacteria but overuse can contribute to increased antimicrobial resistance and cause unwanted side effects in individual animals. Increasing antimicrobial resistance is a growing global threat that can lead to therapy failure and a future with incurable bacterial diseases. Expected benefits of using antibiotics should therefore be weighed against potential unwanted effects.